Increased hydrophobicity of CRYGD p.(Ala159ProfsTer9): Suspected cause of congenital cataracts in a large Chinese family. Issue 10 (23rd July 2020) - Lin, Meina; Jin, Ying; Chen, Xinren; Sui, Yu; Li, Yan; Li, Huan; Ni, Xiang; Zhao, Ning; Lu, Yongping; Jiang, Miao
Abstract: Objective: This study aimed to identify the disease‐causing mutation of congenital cataract disease in a large northeastern Chinese family. Materials and Methods: The subjects' peripheral blood was collected, their genomic DNA was extracted, mutation screening of candidate genes was performed using polymerase chain reaction, and the amplified products were sequenced. Recombinant C‐terminal enhanced green fluorescent protein‐tagged wild‐type or mutant CRYGD was expressed in HEK293T cells, and the expression pattern was observed under a fluorescence microscope. The CRYGD protein mutation was analyzed via bioinformatics analysis. Results: c.475delG, a novel frameshift mutation in CRYGD, was identified in the affected family members. This mutation causes premature termination of the polypeptide, resulting in truncated p.(Ala159ProfsTer9). According to the bioinformatics analysis results, compared with wild‐type CRYGD, p.(Ala159ProfsTer9) exhibits significantly decreased hydrophilicity. Fluorescence microscopy revealed that p.(Ala159ProfsTer9) aggregates in the cell in the form of granular deposits. Conclusion: In this study, the novel frameshift mutation c.475delG, p.(Ala159ProfsTer9) in CRYGD was identified to cause congenital cataracts in a large Chinese family; increased hydrophobicity of p.(Ala159ProfsTer9) protein may be the underlying mechanism. Abstract : A novel frameshift variant, c.475delG in CRYGD was identified in a large family with congenital cataract disease in the Northeast of China, which causes a premature termination of the polypeptide to become p.(Ala159ProfsTer9), decreased hydrophilicity, increased hydrophobicity.